INTERGRASI NILAI-NILAI ISLAM DALAM PRAKTIKUM IPA TERHADAP PENDIDIKAN KARAKTER SANTRI - Dewi, Cindy Olanda; Amruni, Yahya; Fawaida, Ulya (Eduscience : Jurnal Ilmu Pendidikan, 2021)
Education is an effort to promote the growth of character, mind in one's body, where these parts are very important to advance the perfection of children's lives. The purpose of this study was to analyze whether students of science students carry out science practicum by applying the integration of Islamic values. The research method used in this design is descriptive qualitative. The character values obtained in the science practicum by students are discipline, independent, objective, thorough, responsible, helpful and tolerant. Keywords: Character education, integration of Islamic values, science practicum, student